PERBANDINGAN GEJALA KEJADIAN IKUTAN PASCA IMUNISASI SETELAH VAKSIN COVID-19 ASTRAZENECA PERTAMA DAN KEDUA DI CENTRAL VAKSINASI UTA 45 JAKARTA - Lukas, Stefanus; Ramatillah, Diana Laila; Aldi, Yufri; Wahyuni, Fatma Sri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Post-Immunization Adverse Events (AEFI) are common among vaccine participants. AEFI needs to be evaluated because Covid-19 vaccination is an effort to prevent Covid-19 infection which is still relatively new and people are still afraid of post-immunization adverse events occurring. In order for community participation to increase, it is deemed necessary to carry out an AEFI evaluation for both the first dose and the second dose (complete dose). This study aims to evaluate the symptoms of AEFI 1 with AEFI 2 by measuring the number of respondents who caused local and systemic reactions after COVID-19 vaccination. The retrospektive and prospective cross sectional study were used in this study with about 113 Astrazeneca vaccine participants at the UTA'45 Jakarta vaccine center and the data met the inclusion and exclusion criteria. Data was collected through questionnaires, AEFI forms and interviews based on symptoms of local and systemic reactions. Of the 113 participants, 29 were female, while 84 were male and the reactions they caused were different, such as pain, redness, swelling at the injection site, such as fever, muscle aches throughout the body, joint pain and also weakness. Comparison of symptoms of local and systemic reaction between KIPI 1and KIPI 2. In those without symptoms, there was increase number, but in those with symptoms, the number of respondens decrease, and statistically there was sig, P value <0,05.